0883 EEG Connectivity Markers In Combat-exposed Veterans With PTSD. (12th April 2019) - Laxminarayan, Srinivas; Ramakrishnan, Sridhar; Wang, Chao; Germain, Anne; Reifman, Jaques
Abstract: Introduction: Measures of brain connectivity using electroencephalography (EEG) have been shown to provide insights into the functional neuroanatomical underpinnings of normal and abnormal cognitive processes during wakefulness, including learning and memory. However, the body of work on EEG connectivity is non-existent for PTSD, despite its well-established association with sleep disturbances. Here, we explore the alterations in EEG connectivity during sleep in PTSD subjects. Methods: We collected 64-channel EEG recordings from 78 combat-exposed veterans during two consecutive nights of sleep. We computed two connectivity measures, coherence and the weighted phase lag index (wPLI), for each EEG channel-pair across three sleep stages [rapid eye movement (REM) and non-REM stages 2 (N2) and 3 (N3)] and five frequency bands. We examined the median values of these measures in nine region-of-interest (ROI) pairs consisting of six bilateral brain regions (left and right frontal, central, and parietal regions). We split the study data into two subsets of consecutive subjects for: 1) discovery of discriminatory connectivity markers [N = 47, 18 PTSD] and 2) marker validation [N = 31, 13 PTSD]. Results: In the discovery subset, left-right parietal ROI coherence in the theta band (4-8 Hz) during REM sleep was higher in subjects with PTSD compared to controls on both nights [Cohen's d, effect sizes of 0.89 (night 1) and 0.72 (night 2)]. Connectivity in the N2 and N3 alpha band (8-12 Hz) measured by wPLI was higher in PTSD in five ROI pairs, with effect sizes ranging from 0.52 to 1.44 across both nights. The effect was most prominent for the left-right parietal ROI pair during N2 sleep [effect sizes of 1.27 (night 1) and 1.43 (night 2)]. These results were replicated in the validation subset. Conclusion: Parietal ROI connectivity was significantly higher in PTSD subjects compared to controls in REM theta and NREM alpha bands. These EEG connectivity markers may relate to sleep disturbances and cognitive impairments in PTSD. Support (If Any): This work was sponsored by the Military Operational Medicine Program Area Directorate of the U.S. Army Medical Research and Materiel Command, Ft. Detrick, MD.